2005
DOI: 10.1038/sj.hdy.6800639
|View full text |Cite
|
Sign up to set email alerts
|

Long-term stability of allozyme frequencies in a wood lemming, Myopus schisticolor, population with a biased sex ratio and density fluctuations

Abstract: Wood lemming (Myopus schisticolor) populations are characterized by female biased sex ratios and cyclic variations in population size. Both of these characteristics are assumed to reduce genetic variation and thus affect the evolutionary adaptation of the species. We addressed these questions by studying the genetic structure of a wood lemming population from eastern Finland by isozyme markers during a 21-year period, which corresponds to 40-50 generations. Contingency tests showed that genotypic proportions c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…Other behavioural studies have demonstrated that arvicoline rodent dispersal often is negatively density dependent (Smith & Batzli, 2006;Pilot et al, 2010). Such dispersal results in a stable level of genetic variation throughout the cycle which is in agreement with empirical data collected in other species (Vuorinen & Eskelinen, 2005;Ehrich et al, 2009). On the other hand, Le Galliard et al…”
Section: (B) Prediction 2: Population Cycles Cause Temporal Fluctuatisupporting
confidence: 89%
“…Other behavioural studies have demonstrated that arvicoline rodent dispersal often is negatively density dependent (Smith & Batzli, 2006;Pilot et al, 2010). Such dispersal results in a stable level of genetic variation throughout the cycle which is in agreement with empirical data collected in other species (Vuorinen & Eskelinen, 2005;Ehrich et al, 2009). On the other hand, Le Galliard et al…”
Section: (B) Prediction 2: Population Cycles Cause Temporal Fluctuatisupporting
confidence: 89%
“…No finite population is genetically stable over time because of genetic drift. Shifts in gene frequencies are expected, particularly in organisms that have small or cyclically fluctuating populations (Vuorinen & Eskelinen 2005). The low value of Nef corresponded well with the small effective population size.…”
Section: Discussionmentioning
confidence: 71%
“…Small populations tend to fix an appreciable fraction of the genetic load via genetic drift, resulting in elevated levels of among-population inbreeding (Keller & Waller 2002). Density fluctuations in small mammals reduce the effective population size substantially, which is expected to lower genetic diversity and cause inbreeding (Vuorinen & Eskelinen 2005). Populations of T. triton are characterized by marked instability in population size, with density often varying fivefold or more from year to year (Zhang & Wang 1998).…”
Section: Discussionmentioning
confidence: 99%
“…All markers were highly polymorphic and allelic richness indicated similarly high level of genetic variation. Such maintenance of high genetic variation, despite great fluctuations in population density and thus possible threat of repetitive bottlenecks, has already been observed in yellow‐necked mouse (Gortat et al., ; Kozakiewicz et al., ; Rico et al., ) and in several vole species (e.g., Aars et al., ; Berthier et al., , ; Ehrich & Jorde, ; Ehrich et al., ; Gauffre, Estoup, Bretagnolle, & Cosson, ; Gauffre et al., ; Plante, Boag, & Bradley, ; Redeker et al., ; Rikalainen et al., ; Vuorinen & Eskelinen, ). The authors explained a minor impact of often dramatic decline in population size (up to 90% of population; Rikalainen et al., ) by constant and relatively large effective population size, intense migration negatively correlated with density, and the consequential accumulation of new alleles during the population peaks.…”
Section: Discussionmentioning
confidence: 75%